Pengaruh iklan dan harga terhadap brand equity sepatu nike - Yasri, Yasri; Septrizola, Whyosi; Nofriyanti, Monica (Jurnal Kajian Manajemen Bisnis, 2018)
The purpose of this research is to analyze (1) the influence of the advertisement toward brand equity of nike (2) the influence of the price toward brand equity of nike (3) the influence of the advertisement and price toward brand equity of nike. The population in this research is the entire people in Padang who ever wear Nike with samples 100 people. The data of this research are primary data and secondary data. The data was analyzed with multiple regression analysis. The results of this research shows that: (1) the advertisement has positive significant influence toward brand quality of nike (2) the price has positive significant influence toward brand quality of nike (3) the advertisement and price have positive significant influence toward brand quality of nike.Keywords: Brand equity; advertisement; price.